FAKTOR RISIKO ERGONOMI PADA KARYAWAN DI PABRIK PEMBUATAN MINUMAN KEMASAN, INDONESIA - Ratih Pramitasari; Wongsa Laohasiriwong (VISIKES: Jurnal Kesehatan Masyarakat, 2017)
Implementation of inappropriate ergonomics in worker can cause health problems. Musculoskeletal Disorders (MSDs) is one of the health problems that often occur due to improper application of ergonomics. Every step in this beverage factory mostly has the potential for ergonomic risk. This research is a quantitative research with cross sectional study design. Thetotal sample size of 309 has been systematic randomly selected from each department with proportional to size of the population. Data collection tools using BRIEFTM Survey and analyze the data with STATA. BRIEFTM igured the risk associated with posture, force, duration and incidence frequency of nine areas of the body. The results showed the prevalence of ergonomic risk occurring on the left and right sides of the elbows (73.14%). The prevalence of middleergonomic risk on the left side and wrist is 55.99% and right side 55.02% then the left side of the shoulder is 77.02% and the right side 63.11% after being behind is 55.02%. Suggestions for the company should perform particular program about the proper ergonomic position and working order in each department at the beverage factory.